Arbeitszeiten von Vätern: Welche Rolle spielen betriebskulturelle und betriebsstrukturelle Rahmenbedingungen? - Janine Bernhardt; Mareike Bünning (Journal of Family Research, 2017)
Many fathers would like to work less, but they do not reduce their working hours. Studies on the role of workplace organizations for work-family balance point to adverse working conditions as a major obstacle. Quantitative studies, however, are still rare due to the lack of data resources. This paper uses an AID:A add-on survey of 878 parenting couples from 2015 to study the relationships between cultural and structural workplace conditions and fathers’ working times. We differentiate between part-time work, contractual and actual working hours. The results show a robust relationship between fathers’ inclination to work reduced hours and the extent to which formal, universal and transparent policies exist in their workplaces. Perceptions of a strong ideal-worker norm and a supportive culture of temporary replacement are particularly relevant for whether fathers manage to comply with their contractual working hours. Surprisingly, fathers tend to have longer contractual hours, the more they feel supported by their supervisors. The results also indicate that cultural workplace conditions that support shorter working hours of fathers can be found in many economic sectors and companies of different sizes.